English Language Learning Strategies on Grade 8 Students’ Proficiency - Maldonado, Khate (Journal of Interdisciplinary Perspectives, 2025)
The main thrust of this undertaking was to determine the level of adoption of English Language learning strategies and proficiency among Grade 8 students. The study was quantitative research that employed a descriptive correlational research design consisting of 20 respondents in each section and 300 sample sizes out of 600 respondents selected through Stratified Random Sampling. The results revealed that all six language learning strategies, memory, cognitive, comprehension, metacognitive, affective, and social, were manifested by Grade 8 students in varying degrees. There is a significant difference between the assessments of the English teachers and learners on the level of manifestation of adoption of English language learning strategies. Moreover, there is a significant relationship between the level of manifestation of adoption of English language learning strategies and proficiency level among Grade 8 learners. Ultimately, differences between English teachers and learners have nothing to do with students’ proficiency, as results transcend their adoption of language learning strategies. Hence, the proposed action plan, SCALE, might aid in developing high language proficiency in any existing learning environment.